Developmental Exposure to a Mixture of 23 Chemicals Associated With Unconventional Oil and Gas Operations Alters the Immune System of Mice. (1st May 2018) - Boulé, Lisbeth A; Chapman, Timothy J; Hillman, Sara E; Kassotis, Christopher D; O'Dell, Colleen; Robert, Jacques; Georas, Steve N; Nagel, Susan C; Lawrence, B Paige
Abstract: Chemicals used in unconventional oil and gas (UOG) operations have the potential to cause adverse biological effects, but this has not been thoroughly evaluated. A notable knowledge gap is their impact on development and function of the immune system. Herein, we report an investigation of whether developmental exposure to a mixture of chemicals associated with UOG operations affects the development and function of the immune system. We used a previously characterized mixture of 23 chemicals associated with UOG, and which was demonstrated to affect reproductive and developmental endpoints in mice. C57Bl/6 mice were maintained throughout pregnancy and during lactation on water containing two concentrations of this 23-chemical mixture, and the immune system of male and female adult offspring was assessed. We comprehensively examined the cellularity of primary and secondary immune organs, and used three different disease models to probe potential immune effects: house dust mite-induced allergic airway disease, influenza A virus infection, and experimental autoimmune encephalomyelitis (EAE). In all three disease models, developmental exposure altered frequencies of certain T cell sub-populations in female, but not male, offspring. Additionally, in the EAE model disease onset occurred earlier and was more severe in females. Our findings indicate that developmental exposure to this mixture had persistent immunological effects that differed by sex, and exacerbated responses in an experimental model of autoimmune encephalitis. These observations suggest that developmental exposure to complex mixtures of water contaminants, such as those derived from UOG operations, could contribute to immune dysregulation and disease later in life.